Psychological effects of the COVID-19 pandemic on dentistry: A systematic review study - Niloufar Abedi (Wolters Kluwer Medknow Publications, 2021)
The outbreak of the COVID-19 epidemic started in late 2019 in Wuhan, China, causing many psychological and occupational effects for the medical staff, including dentists and all those who work to promote oral health. The present systematic review study investigates the psychological causes and effects of the COVID-19 epidemic outbreak on dentists.Systematic search was performed on valid databases such as Science Direct, Web of Science (WoS), Embase, Cochrane, and Scopus. The English articles published from December 2019 to November 2020 were selected according to the inclusion and exclusion criteria. The quality of the articles was assessed using an existing checklist. Then, their full texts were reviewed to extract the necessary data. Finally, the data were summarized in a table.This systematic review study showed the emergence of psychological symptoms such as fear, anxiety, and stress are the three most common disorders in dentists and all those who work to promote oral health as the medical staff. This pandemic has had occupational and economic consequences for dentists.In general, the research results indicated that the outbreak of COVID-19 had affected the dental profession in two areas: (1) Psychological consequences: Reviewing the articles showed that the essential psychological effects in the dental profession are the fear of infection by patients, anxiety, and stress, respectively. (2) Occupational effects: The second significant consequence of the COVID-19 outbreak was that due to fear and anxiety of getting infected with the virus in the dental environment, containing particles and aerosols from patients' saliva and blood, dentists had to limit doing their jobs in the emergency room and sometimes even closing their offices. This issue may cause economic problems for their professions. There is also a need to allocate additional costs for the provision of sanitary equipment.